Planning of Arrayed Waveguide Grating (AWG) for 16x16 Channels Transmission System of Dense Wavelength Division Multiplexing (DWDM) - Sri Rahayu; Harris Pirngadi (Department of Electrical Engineering ITS and FORTEI, 2018)
Arrayed Waveguide Grating (AWG) Technology, one technique of dividing the channel into smaller sub-channels by adjusting the fixed array length increment. AWG techniques can generate coherent transmissions, which are suitable for Wavelength Division Multiplexing (WDM), to be implemented as multiplexer, demultiplexer, filter, add-drop device, and more. This paper discusses the design planning of AWG parameters operating on C-Band channels (1530-1560 nm), to support the needs of WDM channels, especially Dense-WDM (DWDM). Planning is done using WDM-Phasar tool and through theoretical calculations with MatLab. Theoretical calculations aim to produce ideal design parameters, while through WDM-phasar by adding the device size limit, crosstalk and nonuniformity values, it is expected to obtain more realistic design parameters. The parameters observed include the magnitude of the diffraction order (m), the length of the free propagation range (FPR), the difference in array length (ΔL), the number of arrays (Narray), number of I/O (Nmax) and free spectral range (FSR) channels. By using 16 channels of 100 GHz (0.8 nm) in the C-band, the size of the device (15000x9000 μm2), crosstalk (-35 dB) and nonuniformity (0.5), through WDM-Phasar assistance the AWG parameter 1197.347 μm (FPR), 23.764 μm (ΔL), 41 (m), 56 (Narray), 16 (Nmax) and 11.2 nm (FSR). While ignoring the device size, crosstalk and non-uniformity variables, theoretical parameters were generated at 1308.61 μm, 25.1698 μm, 43.7143, 108 pieces, 27 channels and 21.211 nm, respectively for FPR, ΔL, m , Narray, Nmax and FSR. or WDM system capacity (16x16). Keywords: AWG, WDM, C-Band, crosstalk, non-uniformity